Survival outcomes in node-positive non-metastatic bladder cancer: An analysis of the national cancer database. Issue 4 (2nd October 2022) - Elbakry, Amr A; Trump, Tyler; Ferari, Christopher; Mattes, Malcom D; Luchey, Adam
ABSTRACT: Introduction: Clinically node-positive non-metastatic bladder cancer (cN+) has been the target of several studies aiming to establish a standard of care for this population. Limited studies have shown a survival benefit for various multimodal therapy approaches. The role of radiation therapy has not been well established. Our study aims to study the trends of the reported treatment options offered to patients with cN+ bladder cancer in a national database and to evaluate the effect of various treatments, including radiation, on survival. Methods: The National Cancer Database (NCDB) was used to identify cN+ bladder cancer patients who received chemotherapy alone or in combination with radical cystectomy (RC) or radiotherapy. 3, 481 patients were included and divided into 4 groups: chemotherapy only, chemotherapy and RC, chemotherapy and radiation therapy, and chemotherapy, RC, and radiation therapy. Demographic data was compared using ANOVA for continuous variables, and Chi-square for categorical variables. Multivariable analysis was done to compare groups using a multinomial logistic regression model. Kaplan-Meier test was used for survival analysis and Cox-Regression was used for multivariable survival analysis. Results: Patients undergoing RC were significantly younger ( P <0.001). There was a significant difference between the groups regarding racial distribution, facility-type and insurance status. There was no difference in gender, Charlsonscore, financial or educational status. Patients who underwent combination therapy with chemotherapy and RC were found to have the longest median survival time at 27 months. Multivariable analysis showed that final treatment, age, sex, Charlsoncomorbidity score, TNM edition and facility-type were significant survival predictors. Race, insurance and financial status failed to maintain significance. There was no survival difference between the chemotherapy group and chemo-radiotherapy group. Conclusions: The combination of surgery and chemotherapy achieves statistically significant superior survival in cN+ bladder cancer. Adding radiotherapy to chemotherapy did not improve survival in this group of patients. Abbreviations: (cN+): Clinically node-positive non-metastatic, (MIBC): Muscle invasive bladder cancer, (NCDB): National Cancer Database, (NAC): Neoadjuvant chemotherapy, (RC): Radical Cystectomy